2006
DOI: 10.1074/jbc.m507227200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Transactivation of Pax6 by Homeodomain-interacting Protein Kinase 2

Abstract: Pax6 is a transcriptional activator that contains two DNA binding domains and a potent transcription activation domain in the C terminus, which regulates organogenesis of the eye, nose, pancreas, and central nervous system. Homeodomain-interacting protein kinase 2 (HIPK2) interacts with transcription factors, including homeoproteins, and regulates activities of transcription factors. Here we show that HIPK2 phosphorylates the activation domain of Pax6, which augments Pax6 transactivation by enhancing its inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 52 publications
2
65
1
1
Order By: Relevance
“…S1A). This domain mediates activation of Pax-6 through phosphorylation by p38 MAP kinase and homeodomaininteracting protein kinase 2 (15,16). Several phosphorylation sites have been identified in the PST domain of human and zebrafish Pax-6.…”
mentioning
confidence: 99%
“…S1A). This domain mediates activation of Pax-6 through phosphorylation by p38 MAP kinase and homeodomaininteracting protein kinase 2 (15,16). Several phosphorylation sites have been identified in the PST domain of human and zebrafish Pax-6.…”
mentioning
confidence: 99%
“…Studies have shown that members of the HIPK family interact with, phosphorylate and modulate the function of other homeodomain containing proteins and transcription factors (166)(167)(168)(169)(170), indicating that the HIPKs may have an important role in the control of transcription. Recently it was shown that HIPK2 is expressed in the developing pancreatic epithelium from E12 to E15 and that its expression is confined preferentially to pancreatic endocrine cells later in development (171).…”
Section: Homeodomain Interacting Protein Kinase 2 (Hipk2)mentioning
confidence: 99%
“…PAX6 transcription is regulated by two promoters, P0 and P1, which are remarkably conserved in evolution in both of their nucleotide sequence arrangement and functional control of special and temporal expression of PAX6 in development (Xu and Saunders, 1997;Okladnova et al, 1998a;Williams et al, 1998;Xu and Saunders, 1998;Kammandel et al, 1999;Plaza et al, 1999a;Xu et al, 1999;Tyas et al, 2006), involving multiple transcription factors, such as POU factor Brn-3B, TFCP2, SP1, the basic helix-loop-helix transcription factor NeuroD/BETA2, CCCTC binding factor CTCF, PPARgamma (Plaza et al, 1999b;Zheng et al, 2001;Schinner et al, 2002;Marsich et al, 2003;Li et al, 2006;Wu et al, 2006). PAX6 expression is also regulated by a long range downstream enhancer and is under autoregulation (Grocott et al, 2007) and post modification by HIPK2 and protein phosphatase 1 (Kim et al, 2006;Yan et al, 2007). A promoter-associated polymorphic repeat was found to modulate PAX6 expression in human brain (Okladnova et al, 1998b).…”
Section: Expressionmentioning
confidence: 99%